2018
DOI: 10.3390/su10051579
|View full text |Cite
|
Sign up to set email alerts
|

Public Preferences for the Design of a Farmland Retirement Project: Using Choice Experiments in Urban and Rural Areas of Wuwei, China

Abstract: This paper presents an application of a choice experiment measuring public preferences for a farmland retirement project (FRP) in the Gansu environmental degraded region of China. The project helps improve China's long-term food security, and information on public preferences can be used to cost-effectively design such policies. FRP is conceptualized with four attributes relating to public preferences: Areas enrolled in the program, duration of the contract, priority zone for conservation, and vegetation type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A recent research paper focused only on the financial literacy of Chinese citizens in urban areas and found that barely more than half of the citizens presented a low level of financial literacy (Niu et al, 2020). Another research article explores the differences between the willingness to pay for a farmland retirement project (FRP) of urban and rural residents (Yao et al, 2018); however, it employed a logit model that can hardly explain causal relationships among variables in more profound dimensions. Rethinking Chinese social security (pension coverage, medicare service, and provident fund) to pursue rural-urban harmonization, to rural citizens, reflects the continued unequal rights to employment and the infringement of legitimate rights and interests.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…A recent research paper focused only on the financial literacy of Chinese citizens in urban areas and found that barely more than half of the citizens presented a low level of financial literacy (Niu et al, 2020). Another research article explores the differences between the willingness to pay for a farmland retirement project (FRP) of urban and rural residents (Yao et al, 2018); however, it employed a logit model that can hardly explain causal relationships among variables in more profound dimensions. Rethinking Chinese social security (pension coverage, medicare service, and provident fund) to pursue rural-urban harmonization, to rural citizens, reflects the continued unequal rights to employment and the infringement of legitimate rights and interests.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…A notable recent development is in the use of CEs to inform the design of policies or programmes, whereby attributes are defined in terms of various components of policy design, rather than characteristics of the goods themselves. Applications of this kind include investigation of water quality improvements (Hanley et al., 2006), development policy (James, 2010), farmers’ preferences for disease-free zones (Otieno et al., 2011), consumer preferences for quality and safety attributes in artisanal fruit juices (Otieno and Nyikal, 2017), consumer preference for vitamin-A fortified sugar (Pambo et al., 2017), public preferences for design of farmland retirement projects (Yao et al., 2018), improving the design of agri-environment schemes (Latacz-Lohmann and Breustedt, 2019) and consumer willingness to pay for chicken welfare attributes (Otieno and Ogutu, 2019). In the present study, the CE method is applied to inform policy on the design of foreign land leases in Kenya.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, 'water quality in Hongyashan Reservoir' is recommended to be selected as an attribute. information of parameters to be estimated to minimise standard errors of the estimates (Yao et al, 2018). Accordingly, we used an effective experimental design method for the experimental design considering a priori information of household payment; that is, the effect of household payment on utility must be negative.…”
Section: Choice Experiments Designmentioning
confidence: 99%